Distracted in the digital age: unveiling cyberslacking habits among university students / Sharidatul Akma Abu Seman ... [et al.] - Abu Seman, Sharidatul Akma; Mohd Hashim, Maryam Jameelah; Zainal, Nor Zalina; Mohd Ishar, Nor Irvoni (UiTM Press, 2024)
The integration of digital devices into educational contexts has become pervasive in an era characterised by fast technological innovation. However, the integration of internet connectivity as a tool to enhance the educational experience presents challenges for both university learners as well as educators that go beyond the traditional boundaries of the classroom. One notable difficulty involves the inclination of students to shift their focus towards things unrelated to their academic pursuits, sometimes referred to as “cyberslacking.” Within the realm of education, this phenomenon pertains to the utilization of technology for non-academic endeavors. The objective of this study is to examine students’ cyberslacking continuous behavior in the context of online classrooms. The study sample comprised 387 undergraduate students who were assessed for their engagement in cyberslacking behaviours. PLS-SEM is employed for the analysis of data through the utilisation of an online survey methodology. The results of the study suggest that factors such as addiction, development, and rehabilitation have a crucial role in predicting ongoing cyberslacking behaviour. Furthermore, deviance was found to influence students’ cyberslacking intentions. The findings of this study lend considerably to our understanding of the pervasive cyberslacking behaviours of Malaysian university students. These findings not only cast light on the factors influencing the continuous engagement in cyberslacking, but also offer valuable insights to the broader academic community, including researchers and educators who are interested in establishing effective policies and interventions to tackle the problem of Internet abuse in educational environments. The discussion encompasses the theoretical and practical consequences of the findings.